Development of a novel cell line‐derived xenograft model of primary herpesvirus 8‐unrelated effusion large B‐cell lymphoma and antitumor activity of birabresib in vitro and in vivo. (24th November 2021) - Nishimori, Tomohiro; Higuchi, Tomonori; Hashida, Yumiko; Ujihara, Takako; Taniguchi, Ayuko; Ogasawara, Fumiya; Kitamura, Naoya; Murakami, Ichiro; Kojima, Kensuke; Daibata, Masanori
Abstract: Background: Primary human herpesvirus 8 (HHV8)‐unrelated effusion large B‐cell lymphoma is a clinical disease entity distinct from HHV8‐positive primary effusion lymphoma (PEL). However, the lack of experimental HHV8‐unrelated effusion large B‐cell lymphoma models continues to hinder the pathophysiologic and therapeutic investigations of this disorder. Methods: The lymphoma cells were obtained from the pleural effusion of a patient with primary HHV8‐unrelated effusion large B‐cell lymphoma and cultured in vitro . Results: We established a novel HHV8‐unrelated effusion large B‐cell lymphoma cell line, designated Pell‐1, carrying a c‐MYC rearrangement with features distinct from those of HHV8‐positive PEL. Moreover, we developed an HHV8‐unrelated effusion large B‐cell lymphoma cell line‐derived xenograft model. Pell‐1 cells induced profuse lymphomatous ascites and subsequently formed intra‐abdominal tumors after intraperitoneal implantation into irradiated nonobese diabetic/severe combined immunodeficient mice. Thus, this xenograft mouse model mimicked the clinical phenomena observed in patients and recapitulated the sequential stages of aggressive HHV8‐unrelated effusion large B‐cell lymphoma. The bromodomain and extraterminal domain (BET) inhibitors JQ1 and birabresib (MK‐8628/OTX015) reduced the proliferation of Pell‐1 cells in vitro through the induction of cell cycle arrest and apoptosis. The antitumor effect of BET inhibition was also demonstrated in vivo, as birabresib significantly reduced ascites and suppressed tumor progression without apparent adverse effects in the xenografted mice. Conclusion: These preclinical findings suggest the therapeutic potential of targeting c‐MYC through BET inhibition in HHV8‐unrelated effusion large B‐cell lymphoma. Abstract : A new herpesvirus 8 (HHV8)‐unrelated effusion large B‐cell lymphoma cell line, Pell‐1, with a c‐MYC rearrangement induced profuse lymphomatous ascites and subsequently formed intra‐abdominal tumors after intraperitoneal implantation into irradiated NOD/SCID mice. This xenograft model mimicked the clinical phenomena observed in patients and recapitulated the sequential stages of aggressive HHV8‐unrelated effusion large B‐cell lymphoma. The BET inhibitor birabresib significantly suppressed effusion formation and tumor progression in mice.